2022
DOI: 10.3389/fneur.2022.801121
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of CPAP Treatment on Resting-State Network Centrality in Obstructive Sleep Apnea Patients

Abstract: Background and ObjectivesObstructive sleep apnea (OSA) is the most common sleep disorder and previous studies have shown that OSA patients suffer from brain network impairments associated with cognitive deficits, and continuous positive airway pressure (CPAP) treatment can improve clinical symptoms. However, the relationship between CPAP treatment and brain network changes remains unclear. This study explored the characteristics of brain network changes in OSA patients before (pre-CPAP) and after one month of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
1
8
0
1
Order By: Relevance
“…Park et al ( 46 ) found that OSA showed decreased network integration connectivity in the cerebellum, which was susceptible to hypoxia or ischemia. After long-term CPAP treatment, patients with OSA may have increased cerebellar volume ( 47 , 48 ). In our study, even one-night CPAP treatment can reverse the brain function of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al ( 46 ) found that OSA showed decreased network integration connectivity in the cerebellum, which was susceptible to hypoxia or ischemia. After long-term CPAP treatment, patients with OSA may have increased cerebellar volume ( 47 , 48 ). In our study, even one-night CPAP treatment can reverse the brain function of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Further randomized control trial showed that the adherent continuous positive airway pressure (CPAP) therapy could improve the sleep-related erectile function in OSA patients, possibly via attenuating OSA-induced hypoxia. 12 13 Another cross-sectional study enrolling 754 males reported that male night shift workers had lower International Index of Erectile Function (IIEF) scores than male non-night shift workers. 11 Additionally, according to Seehuus and Pigeon, 14 insomnia severity was significantly associated with sexual dysfunction and sleep disorders may function in the occurrence of ED.…”
Section: Introductionmentioning
confidence: 99%
“…The morphologically detectable changes are partially reversible by successful PAP therapy 66 121 122 123 . The irreversible morphologic brain changes are associated with residual daytime sleepiness despite adequate therapy 64 78 124 .…”
Section: Obstructive Sleep Apnea Syndrome and Cognitionmentioning
confidence: 99%